The effectiveness of gamification through classroom leaderboards for student engagement - Abdul Halim, Fauziah Saadah; Ahmad Buhari, Turisiana (UiTM Press, 2022)
Universities, researchers and practitioners are looking for effective ways to engage, enhance, and promote students' learning in the classroom. Gamification is the integration of game-like design elements into non-game context to motivate action, engage, and solve problems. This paper presents the effectiveness of gamification through leaderboards to improve student engagement in subjects for Company Website Design (EIC552) and Communication through Drama (EPE530) at Akademi Pengajian Bahasa, Universiti Teknologi MARA. Questionnaires were given to examine the effects of gamification on student learning and engagement. Results suggest that gamification through leaderboards are effective in improving student participation and encouraging extracurricular learning.